Suppressor effects of carrots on azoxymethane/dextran sulfate sodium-induced colon cancer according to cultivation method - Pan, Yanni; Lee, Yeon-Jun; Kim, Jin Hyeop; Song, Min Ji; Kwack, KyuBum; Park, Seung-Hwan; Sin, Sin-Il; Chung, Ji Hyung; Park, Kun-Young (Frontiers in Immunology, 2025)
IntroductionThis study investigated the suppressor effects of carrots depending on cultivation method on AOM/DSS-induced colon cancer in mice by examining cell apoptosis, inflammation response, and metabolites. Carrots grown using different fertilizers significantly suppressed tumor development by modulating cell apoptosis and inflammatory responses in our experimental settings.Methods and ResultsNaturaldream Fertilizer Carrot (NFC) cultivated with deep sea water minerals (DSWM) showed effectively increased the expression of apoptosis-related genes and proteins including p53, p21, Bim, Bad, Bax, Bak, Caspase 9, and Caspase 3 in colon tissue, while inhibiting the production of inflammatory factors and related genes and proteins such as TNF-a, IL-1b, IL-6, IFN-g, NF-kB, and iNOS in serum, spleen cells, and liver tissues. Intestinal microbiota analysis revealed a distinct composition in mice receiving carrots compared to the control group, with accumulation of intestinal microorganisms such as Lachnospiraceae, and Mucispirillum schaedleri closely associated with anti-tumor effects.Discussion and ConclusionOverall, our results indicate that carrots, especially carrots grown with DSWM fertilizers, play a crucial role in inhibiting AOM/DSS-induced colon cancer in mice by regulating cell apoptosis and inflammation responses. The present findings provide valuable insights for further exploration of carrots depending on the cultivation method, as a potential dietary source against colon cancer.